2021
DOI: 10.21109/kesmas.v16i3.4384
|View full text |Cite
|
Sign up to set email alerts
|

Association between Self-Reported Fatigue and Sarcopenia Measures among Elderly in Selangor, Malaysia

Abstract: The association between fatigue and sarcopenia is not well understood, therefore, this study aimed to compare the sarcopenia measures among elderly with mild and severe fatigue and to determine whether fatigue severity is associated with sarcopenia measures. This was a cross-sectional study conducted on201 elderly (age = 68.45±6.30 years). The elderly was classified into either mild or severe fatigue based on the Fatigue Severity Scale (FSS), meanwhile, sarcopenia measures include SARC-F score, muscle mass (AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…low gait speed) is used to determine sarcopenia severity (24) . Recently, Justine et al (33) reported associations of fatigue severity (assessed with the fatigue severity scale) with the SARC-F questionnaire (acronym for the poor Strength, need of Assistance with walking, impaired Rising from a chair, difficulty at Climbing stairs and history of Falls), calf circumference, muscle strength and gait speed. Wyness et al (34) found an association of low gait speed with higher scores for physical fatigue, reduced activity and reduced motivation.…”
Section: Sarcopenia Frailty and Fatiguementioning
confidence: 99%
“…low gait speed) is used to determine sarcopenia severity (24) . Recently, Justine et al (33) reported associations of fatigue severity (assessed with the fatigue severity scale) with the SARC-F questionnaire (acronym for the poor Strength, need of Assistance with walking, impaired Rising from a chair, difficulty at Climbing stairs and history of Falls), calf circumference, muscle strength and gait speed. Wyness et al (34) found an association of low gait speed with higher scores for physical fatigue, reduced activity and reduced motivation.…”
Section: Sarcopenia Frailty and Fatiguementioning
confidence: 99%